Trade in tasks, tariff policy and effective protection rates - Antonia Diakantoni; Hubert Escaith (World Trade Organization (WTO), 2014)
Building on the results of the OECD-WTO Trade in Value-Added TiVA database, the paper analyses the evolution of effective protection in about 50 developed and developing countries from 1995 to 2008. The paper reviews also the role of preferential agreements on effective protection as well as the impact of tariffs on the production costs of services. A final chapter is dedicated to exploring the underlying patterns that may exist beyond the EPR profiles.
Keywords: C38; C67; D24; F13; F23; F60; O19; 330; Tariff; Effective Protection; Trade in Value Added; International Outsourcing and Competitiveness